Questioning the relevance of alienability in Arawak linguistics: an innovative analysis of possession in Mojeño Trinitario - Rose Françoise (Linguistics, 2023)
This article presents an original analysis of possession in Mojeño Trinitario, an Arawak language, teasing apart the levels of lexical possessive noun classes, morphological derivation between noun classes, and adnominal possessive constructions. The three possessive noun classes (obligatorily prefixed, optionally prefixed and non-prefixable) do not exactly correspond to the three possessive noun classes of the traditional analysis of Arawak languages, as in the analysis proposed here some of the traditionally called “alienable” nouns, i.e. nouns occurring as either possessed or unpossessed, are classified as non-prefixable nouns because they need some additional derivational morphology to be prefixable. The two adnominal possessive constructions (basic, through prefixation and modification; and indirect, via a generic possessive noun) are described, and their distribution is discussed. The article then addresses the question of how the notion of “alienability contrast” could explain the phenomena described, at either the lexical or phrasal level. In the process, it offers frequency counts on how often nouns of the different possessive classes occur as possessed in discourse, and it discusses whether the three noun classes are open or closed classes. It concludes that the alienability contrast is at best only a partial explanation for the expression of possession in Mojeño Trinitario. This article ends by developing how this innovative account of possession in Mojeño Trinitario applies to other Arawak languages.